ANALISIS PERBANDINGAN ANTARA KINERJA SAHAM JAKARTA ISLAMIC INDEX (JII) DAN NON-JAKARTA ISLAMIC INDEX (NON-JII) DI BURSA EFEK INDONESIA (BEI) SELAMA PERIODE TAHUN 2007 –2009 - Siti Nurlatifah (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2015)
The purpose of this research is to investigate there or no significant difference between performance Jakarta Islamic Index (JII) stock and Non-Jakarta Islamic Index (Non-JII) stock on the Indonesia Stock Exchange (IDX) during the period 2007-2009. On this research showed is not there enough evidence empiris to show that performance JII stock difference with Non-JII. Performance return JII stock relative same with return Non-JII stock, for standar deviation risk of JII stock more good in the comparatif with non JII stock and also is not there enough evidence empiris to show that beta JII stock difference with Non-JII stock, Beta JII stock average in bottom number 1, where beta Non-JII stock also same in bottom number 1, but the risk more small in comparatif with Non-JII stock.